Review on Steganography Methods in Multi-Media Domain - Din, Roshidi; Mahmuddin, Massudi; Jabbar Qasim, Alaa (International Journal of Engineering and Technology, 2019)
Steganography is one area in information security that is able to conceal the secret message in any media to avoid the intruders. In this paper, the review of steganography is done in certain media such as image, text, audio, and video. It analyses some of the techniques that applied steganography to discover the development of the techniques to cover a secret message. It is expected that this paper is able to describe the implementation of steganography by previous researchers on their efforts. Â